2021
DOI: 10.1016/j.coviro.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with SARS-CoV-2: are interferons friends or foes in COVID-19?

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 97 publications
(95 reference statements)
2
27
0
Order By: Relevance
“…Compromised activation of type I IFN responses in SARS-CoV-2 patients are associated with disease severity. However, other studies have shown increased IFN activation to be associated with exacerbated COVID-19 21 .…”
Section: Introductionmentioning
confidence: 90%
“…Compromised activation of type I IFN responses in SARS-CoV-2 patients are associated with disease severity. However, other studies have shown increased IFN activation to be associated with exacerbated COVID-19 21 .…”
Section: Introductionmentioning
confidence: 90%
“…In infected cells, the host lncRNAs might modulate IFN induction for antiviral response by interacting with different components in the IFN induction pathway (reviewed [8,132]). Deregulation of the IFN pathways either by inborn errors or the generation of autoantibodies against type I IFNs or deregulation IFN signaling pathways have been associated with COVID-19 pathogenesis [133][134][135]. JAK-STAT signaling pathway in response to viral infection, in general, is the important component of the interferon response of the host.…”
Section: Mechanism Of Deregulation Of Lncrna and Pcgmentioning
confidence: 99%
“…Type I and III IFNs may be secreted by almost any cell type, whereas type II IFN production is restricted to immune cells, particularly T and Natural Killer (NK) cells. Innate immunity plays a major role in defending against emerging pathogens like SARS-CoV-2, the causative agent of COVID-19 [7][8][9][10][11]. This respiratory virus has a profound global impact both on a socioeconomic level and as a major threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these evasion mechanisms SARS-CoV-2 still remains sensitive towards all types of IFNs, with types II and III being most effective [12,[16][17][18][19]. Importantly, early induction of high levels of IFNs in patients were reported to prevent severe COVID-19 [8,9]. Conversely, inborn defects in the IFN system or auto-antibodies against type I IFNs are frequently associated with severe disease [10,11].…”
Section: Introductionmentioning
confidence: 99%